THE EFFECT OF ACCOUNTING CONSERVATISM ON INFORMATION ASYMMETRY: EVIDENCE FROM COMPANIES LISTED ON THE IRAQ STOCK EXCHANGE - Hasan Talib Hashim; Dr. Fatima Jasim Mohammed; Dr. Abdulhussein Towfeeq shibli (Scholar Express Journals, 2022)
The study of companies listed on the Iraqi Stock Exchange (ISX) examines the effect of accounting conservatism on information asymmetry. To determine accounting conservatism, a scale (Givoly & Hayn, 2000) was used. High/low spreads were used to measure information asymmetry. The data is derived from the annual financial statements and trading bulletins from 2015 to 2019. According to the results of the statistical analysis of the current study, there is a statistically significant effect of accounting conservatism in information asymmetry with a significant level of 0.001.
Keywords: accounting conservatism; information asymmetry; High-Low spread